Genomic and clinical characteristics of carbapenem-resistant Enterobacter cloacae complex isolates collected in a Chinese tertiary hospital during 2013–2021 - Han, Mei; Liu, Chang; Xie, Hui; Zheng, Jie; Zhang, Yan; Li, Chuchu; Shen, Han; Cao, Xiaoli (Frontiers in Microbiology, 2023)
Objective: To analyze the molecular epidemiology of carbapenem-resistant Enterobacter cloacae complex (CREC) by whole-genome sequencing and to explore its clinical characteristics. Methods: CREC isolates collected in a tertiary hospital during 2013–2021 were subjected to whole-genome sequencing to determine the distribution of resistance determinants, sequence types (STs), and plasmid replicons. A phylogenetic tree of the CREC strains was constructed based on the whole-genome sequences to analyze their relationships. Clinical patient information was collected for risk factor analysis. Results: Among the 51 CREC strains collected, blaNDM-1 (n = 42, 82.4%) was the main carbapenem-hydrolyzing β-lactamase (CHβL), followed by blaIMP-4 (n = 11, 21.6%). Several other extended-spectrum β-lactamase-encoding genes were also identified, with blaSHV-12 (n = 30, 58.8 %) and blaTEM-1B (n = 24, 47.1%) being the predominant ones. Multi-locus sequence typing revealed 25 distinct STs, and ST418 (n = 12, 23.5%) was the predominant clone. Plasmid analysis identified 15 types of plasmid replicons, among which IncHI2 (n = 33, 64.7%) and IncHI2A (n = 33, 64.7%) were the main ones. Risk factor analysis showed that intensive care unit (ICU) admission, autoimmune disease, pulmonary infection, and previous corticosteroid use within one month were major risk factors for acquiring CREC. Logistic regression analysis showed that ICU admission was an independent risk factor for CREC acquisition and was closely related with acquiring infection by CREC with ST418. Conclusion: BlaNDM and blaIMP were the predominant carbapenem resistance genes. ST418 carrying BlaNDM not only was the main clone, but also circulated in the ICU of our hospital during 2019–2021, which highlights the necessity for surveillance of this strain in the ICU. Furthermore, patients with risk factors for CREC acquisition, including ICU admission, autoimmune disease, pulmonary infection, and previous corticosteroid use within one month, need to be closely monitored for CREC infection.